Into the heterogeneities in the Portuguese labour market : an empirical assessment - Martins, Fernando (2019)
This paper provides a comprehensive study of the heterogeneity in the Portuguese labour market. We use Labour Force Survey microdata covering a complete business cycle, from 1998:1 to 2018:1, to evaluate the labour market attachment of several labour states and assess the most suitable allocation of individuals across statuses. We also evaluate the adequacy of the conventional unemployment criteria. Following the relevant strand of literature on this topic, we apply an evidence-based categorisation of labour market status by exploiting the information on the results of the behaviour of non-employed. To that end, we use multinomial and binary logit models of the determinants of transitions of workers across labour market states to test for the equivalence between non-employed groups. We conclude that heterogeneity is an evident feature of the Portuguese labour market, both between and within the conventional non-employment states. In particular, we find that the status comprising those inactive workers which want work constitutes a distinct state in the labour market and displays a transition behaviour closer to unemployment than to the group of inactive workers which do not want work. Moreover, the classification as inactive workers of individuals which report "waiting" as a reason for not having searched for a job, those individuals who have searched for a job but are still considered to be out-of-the-labour-force, as well as those individuals which are due to start work in more than three months might not be reasonable, since they show considerable attachment to the labour market and we reject the pooling of such states with their counterparts.